Place of diagnostic tools in the identification of Anaerobiospirillum succiniciproducens bacteraemia. (June 2016) - Decroix, V.; Pluquet, E.; Choquet, M.; Ammenouche, N.; Castelain, S.; Guiheneuf, R.
Abstract: Anaerobiospirillum succiniciproducens is a rare but potentially lethal pathogen. We report a case of A. succiniciproducens bloodstream infection in a 55-year-old man hospitalized for pelvic trauma. The strain was identified by 16sRNA sequencing after several failures of identification by MALDI-TOF MS. The strain was susceptible to beta-lactam antibiotics and ciprofloxacin, but resistant to macrolides and clindamycin. Identification tools must be improved to enhance our knowledge on this rare pathogen and to define optimal therapy. Highlights: Anaerobiospirillum succiniciproducens is a significant human pathogen. Identification in clinical samples is difficult. 16sRNA sequencing is the best identification tool at the present time. MALDI-TOF databases should include this rare pathogen.